Decolonizing Philanthropy in Building a Theological Framework through Reading the Book Tanbih al- Mughtarrin - Shulhan, Shulhan; Lessy, Zulkipli; Suhadi, Suhadi; Mohammad Mohammad Zidan, Sayed; Fuad, Munawwarul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2026)
Contemporary philanthropy studies are largely shaped by Western epistemological frameworks that conceptualize giving as voluntary charity and humanitarian intervention, often detached from metaphysical accountability and moral discipline. This article aims to reconstruct the theological framework of wealth, philanthropy, and moral responsibility articulated in Tanbih al-Mughtarrin and to examine its epistemic contribution to contemporary debates on philanthropy and moral economy from a decolonial perspective. Using a qualitative library-based method, the study combines theological-textual analysis of the classical work with critical engagement with recent scholarship on philanthropy, Islamic ethics, and moral economy. The findings reveal that the text conceptualizes wealth as a divinely entrusted trust governed by lawful acquisition, ethical stewardship, and obligatory redistribution. Unlike dominant Western paradigms that separate accumulation from redistribution and privilege donor autonomy, the framework integrates production, possession, and circulation within a unified moral economy grounded in accountability (ḥisab), justice, and human dignity (karamah). The study argues that its epistemic contribution lies in proposing an alternative moral ontology in which ownership is understood as trusteeship, philanthropy as obligation rather than voluntarism, and economic activity as inseparable from transcendental accountability. By reconstructing this framework, the article contributes to contemporary efforts to pluralize and decolonize philanthropy studies.